Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1136/gut.47.4.546
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory mediators in human acute pancreatitis: clinical and pathophysiological implications

Abstract: Background-The time course and relationship between circulating and local cytokine concentrations, pancreatic inflammation, and organ dysfunction in acute pancreatitis are largely unknown. Patients and methods-In a prospective clinical study, we measured the proinflammatory cytokines interleukin (IL)-1 , IL-6 and IL-8, the anti-inflammatory cytokine IL-10, interleukin 1 receptor antagonist (IL-1RA), and the soluble IL-2 receptor (sIL-2R), and correlated our findings with organ and systemic complications in acu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
258
0
37

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 353 publications
(314 citation statements)
references
References 43 publications
11
258
0
37
Order By: Relevance
“…However, CRP levels are infl uenced by liver disease ( 11 ), which may be present in many patients with AP who are obese and/or alcoholics. Furthermore, CRP levels peak at 72-96 h aft er symptom onset, which can limit its prognostic accuracy as patients typically present at variable times aft er symptom onset ( 12,13 ). Finally, CRP is a laboratory marker that is not routinely measured in AP patients throughout the world.…”
mentioning
confidence: 99%
“…However, CRP levels are infl uenced by liver disease ( 11 ), which may be present in many patients with AP who are obese and/or alcoholics. Furthermore, CRP levels peak at 72-96 h aft er symptom onset, which can limit its prognostic accuracy as patients typically present at variable times aft er symptom onset ( 12,13 ). Finally, CRP is a laboratory marker that is not routinely measured in AP patients throughout the world.…”
mentioning
confidence: 99%
“…Whereas the initiating events leading to the development of necrosis are still poorly understood, the subsequent infiltration of different leukocyte subsets into the damaged gland are claimed to be the major source for the release of various toxic mediators, such as proteolytic enzymes (Rinderknecht, 1994), oxygen free radicals (Poch et al, 1999;Rinderknecht, 1994), and cytokines (Fink and Norman, 1996). In this setting, potent proinflammatory cytokines, such as tumor necrosis factor-␣ (TNF-␣) and interleukin-1␤ (IL-1␤), have been shown to mediate enhanced local tissue destruction (Denham et al, 1997) and distant organ complications (Mayer et al, 2000;Norman et al, 1997a;Norman, 1998;Ogawa, 1998).…”
mentioning
confidence: 99%
“…Cathepsin-B, a lysosomal cystein protease in the acinar cells, has been studied, and it has been shown to stimulate the conversion of trypsinogen to trypsin directly. Moreover, its complete inhibition blocks 90% of the conversion of trypsinogen to trypsin (1,2,30,31). Cathepsin-B also strongly activates mesotrypsinogen, one of the pancreatic isoforms of trypsinogen.…”
Section: Historymentioning
confidence: 99%
“…As reviewed previously, the pathophysiologic events in acute pancreatitis are initiated and perpetuated by failure of the control of the state of activation of the pancreatic enzymes in the acinar cell and ductal lumen. Some studies have demonstrated that gastric or duodenal feeding increases the production of enzymes by the pancreas, which may further stimulate or aggravate the disease process and cause more complications (1,2,30,31,74).…”
Section: Pain Controlmentioning
confidence: 99%